Protein S Deficiency and the Risk of Venous Thromboembolism in the Han Chinese Population - Wu, Yingying; Liu, Jingdi; Zeng, Wei; Hu, Bei; Hu, Yu; Tang, Liang V. (Frontiers in Cardiovascular Medicine, 2022)
Plasma levels of the anticoagulant cofactor protein S and PROS1 mutation are reported to impart increased risk of thromboembolism in European and south east Asian populations, but the relationship is not yet documented in Han Chinese in population-based study. Therefore, we undertook a case-control study of this relationship among patients with venous thromboembolism, and probed the genetic factors contributing to low protein S deficiency. Among the 603 consecutively recruited venous thromboembolism patients, 51 (8.5%) proved to be deficient in free protein S antigen (lower than 38.6 U/dl), among whom 30 cases were identified to have a causative mutation by direct sequencing. In contrast, six cases (1.0%) of the 584 healthy controls had low free antigen levels, among whom direct sequencing confirmed disease-causing gene mutations in four controls (0.7%). After adjusting for age and gender, the odds ratio of developing venous thromboembolism in individuals with protein S deficiency based on free protein S tests was 8.1 (95% CI = 3.6–19.9, P < 0.001). Gene sequencing yielded 24 different heterozygous mutations in the 34 participants, of which 13 were newly described. 17 (50%) of the 34 mutations in our study cohort occurred in exons 12 and 13, indicating the LGR2 domain to be a hotspot mutation region for the protein. These findings are conducive to the clinical application of protein S assays for the molecular diagnosis of thrombophilia.